Mitochondrial function in Parkinson's disease cybrids containing an nt2 neuron-like nuclear background - Esteves, AR (2008)
Mitochondria likely play a role in Parkinson's disease (PD) neurodegeneration. We modelled PD by creating cytoplasmic hybrid (cybrid) cell lines in which endogenous mitochondrial DNA (mtDNA) from PD or control subject platelets was expressed within human teratocarcinoma (NT2) cells previously depleted of endogenous mtDNA. Complex I activity was reduced in both PD cybrid lines and in the platelet mitochondria used to generate them. Under basal conditions PD cybrids had less ATP, more LDH release, depolarized mitochondria, less mitochondrial cytochrome c, and higher caspase 3 activity. Equivalent MPP+ exposures are more likely to trigger programmed cell death in PD cybrid cells than in control cybrid cells. Our data support a relatively upstream role for mitochondrial dysfunction in idiopathic PD.